2009
DOI: 10.1161/circoutcomes.108.816843
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Postoperative Atrial Fibrillation After Isolated Coronary Artery Bypass Graft Surgery and Long-Term Survival

Abstract: Background-The advancing age and generally increasing risk profile of patients receiving isolated coronary artery bypass graft (CABG) surgery is expected to raise incidence of new-onset postoperative atrial fibrillation (AFIB) resulting in potentially higher risk of adverse outcomes. In the early postoperative course, new-onset post-CABG AFIB is considered relatively easy to treat and is believed to have little impact on patients' long-term outcome. However, little has been done to determine the effect of new-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 31 publications
7
68
1
2
Order By: Relevance
“…Even when using this comprehensive adjustment, POAF remained a significant and independent predictor of longterm mortality. The results of our study, supported by the results of other well-conducted studies in the field of coronary surgery, 1,5,8,11 provide strong evidence for a significant impact of POAF on long-term survival.…”
Section: Impact Of Poaf On Operative Mortalitysupporting
confidence: 87%
See 1 more Smart Citation
“…Even when using this comprehensive adjustment, POAF remained a significant and independent predictor of longterm mortality. The results of our study, supported by the results of other well-conducted studies in the field of coronary surgery, 1,5,8,11 provide strong evidence for a significant impact of POAF on long-term survival.…”
Section: Impact Of Poaf On Operative Mortalitysupporting
confidence: 87%
“…Although POAF appears to be a benign complication in the majority of patients, the present study and other recent studies 1,5,8,12 have pinpointed that POAF is a strong and independent predictor of both operative and late mortality. Patients who develop POAF should be considered at higher risk for adverse outcomes in the short and long term.…”
Section: Discussionsupporting
confidence: 50%
“…The development of AF is extremely common after cardiac surgery and is associated with longer intensive care unit and hospital stays, increased morbidity and mortality, and higher utilisation of healthcare resources [6][7][8][9][10][11]. For these reasons, it is of utmost importance to identify patients who are at risk for the development of postoperative AF (POAF), and to take due precautions in the preoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…SVEC progressing to AF was further characterised by a small prospective study by Wallmann et al, who reported that patients with more frequent SVEC's were at higher risk of developing AF (OR of 9.3, p = 0.01) than those with less frequent supraventricular ectopy. 7 Left atrial size was also significantly larger in the group developing AF compared to those remaining in sinus rhythm.…”
Section: Journal Of Atrial Fibrillation Journal Reviewmentioning
confidence: 91%